Exploring the Development Needs of Geography Laboratories: Infrastructure, Equipment, and Educational Context - Yasmin Fajar Putri Ayu Wardhani; Suleyman Incekara; Adi Jafar; Fajar Wulandari (Future Space: Studies in Geo-Education, 2025)
The Geography Laboratory is essential in supporting learning based on Constructivist Theory. However, public senior high schools in Malang City do not have dedicated laboratory spaces for Geography or Social Sciences subjects. This study aims to analyze the development needs of Geography laboratories based on the materials outlined in the Kurikulum Merdeka. The scope of the laboratory needs examined includes practicum activities, laboratory equipment, laboratory materials, and Geography laboratory space. This study explores these needs from teachers' perspectives. A quantitative research method with a descriptive approach was employed. The study utilized a survey design, involving 24 Geography teachers from all public senior high schools in Malang City as participants. Data collection was conducted through questionnaires, interviews, and documentation. To ensure data validity, methodological triangulation was applied. The collected data are presented in tables, narrative texts, and field documentation images. Findings indicate a significant issue regarding the availability of Geography laboratory equipment and materials, which remain insufficient in schools. However, the study reveals that a dedicated Geography laboratory is not considered essential, as teachers in public senior high schools in Malang City prefer utilizing classrooms and outdoor laboratories for practicum activities.